Pengaruh Persepsi Harga Dan Kemasan Terhadap Keputusan Pembelian Di Toko Alfazza Pasar Cendrawasih Kota Metro - Febriyanto, Febriyanto; Fuadi, Selamet; Hernanda, Reza (Universitas Muhammadiyah Metro, 2023)
The purpose of this research is partially and simultaneously to determine the effect of price andpackaging perceptions on purchasing decisions. The research method uses quantitative. Whilethe sample used is 40 customer respondents who often make purchase transactions. Thesampling technique used purposive sampling. The analysis tool uses multiple multiple regressionwith partial t test decisions, simultaneous f and the coefficient of determination. The results ofthe study prove that purchasing decisions are an approach and problem solving in humanactivities to buy goods and services in fulfilling their wants and needs, including: 1) Attention, 2)Interest, 3) Desire, 4) buying action (action), 5) The stages of this that can lead to priceperceptions and good forms of measurement, so that they can provide purchasing decisions.